1980
DOI: 10.1063/1.439088
|View full text |Cite
|
Sign up to set email alerts
|

The temperature dependence of hydrogen abstraction reactions: F+HCl, F+HBr, F+DBr, and F+HI

Abstract: Time-dependent quantum wave packet studies of the F+HCl and F+DCl reactionsExamination of the Br+HI, Cl+HI, and F+HI hydrogen abstraction reactions by photoelectron spectroscopy of BrHI−, ClHI−, and FHI− Molecular beam scattering experiments on the abstraction and exchange reactions of deuterium atoms with the hydrogen halides HCl, HBr, and HI A laser photolysis/infrared fluorescence technique has been used to study the temperature dependence of the F + HCI, F + HBr, F + DBr, and F + HI absolute rate constants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 27 publications
4
28
0
Order By: Relevance
“…15 Later, Würzberg and Houston measured the absolute rate constant over the range 195 to 373 K, and observed a remarkable nonlinear Arrhenius behavior. 16 A similar study was reported by…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…15 Later, Würzberg and Houston measured the absolute rate constant over the range 195 to 373 K, and observed a remarkable nonlinear Arrhenius behavior. 16 A similar study was reported by…”
Section: Introductionsupporting
confidence: 71%
“…The work of Bulut et al 29 shows that the rate constants predicted by calculations with this PES are an order of magnitude smaller than experimental estimates. 16,17 In addition, they concluded that quantum tunneling will not make a significant contribution to the thermal reaction rates. Sayos et al 22 scaled their PES to mimic the barrier on the LEPS PES used by Ding et al 15 (E a = 1.1 kcal mol À1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimentalists, have focused on the determination of thermal rate constants. Wurzberg et al 10,11 and Moore et al 12 measured absolute rate constants in the temperature range 195-373 K and 195-294 K, respectively, using laser photolysis techniques. The measured thermal rate constants were found to follow a non-Arrhenius behavior over the studied temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…The title reaction has been the subject of many theoretical [1][2][3][4][5][6][7][8][9] and experimental [10][11][12] studies. Experimentalists, have focused on the determination of thermal rate constants.…”
Section: Introductionmentioning
confidence: 99%
“…The X-HF [145][146][147][148][149][150] and X-HCN [151][152][153] PES have also been studied in collision experiments. Recently, strong rotational enhancement has been described for the F + HCl reaction [150,154].…”
Section: A Complexes Containing Halogen Atomsmentioning
confidence: 99%